2020
DOI: 10.1111/jfpp.14826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial replacement of wheat flour by taro and Jerusalem artichoke flours on chemical and sensory properties of tarhana soup

Abstract: Tarhana is a popular traditional fermented food product generally used for soup making in Turkey (Bilgiçli, 2009; Erbaş, Certel, & Uslu, 2005). It is formulated with yogurt, wheat flour, yeast, and various vegetables (tomatoes and onions) and spices (salt, mint, and paprika). The ingredients are mixed, kneaded, and left for fermentation for a suitable period of time (1-7 days; Erbaş et al., 2005). The fermented dough was dried under sun or in oven and then ground to the particle size less than 1 mm (Bilgiçli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
6
17
0
Order By: Relevance
“…Our results demonstrated good agreement with those reported by Cankurtaran et al. (2020). But Aboubakar et al.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results demonstrated good agreement with those reported by Cankurtaran et al. (2020). But Aboubakar et al.…”
Section: Resultssupporting
confidence: 93%
“…The Ca, Fe, K, Mg, P, and Zn content of RTF and CTF were significantly (p < .05) higher than the other raw materials (Table 2). Our results demonstrated good agreement with those reported by Cankurtaran et al (2020). But Aboubakar et al (2008) have reported the Ca, Fe, K, Mg, and Zn content of taro flours as 25.4-192 mg/100 g, 0.24-4.17 mg/100 g, 3.5-59.7 mg/100 g, 32.9-382 mg/100 g, and 0.04-4.28 mg/100 g, respectively.…”
Section: Chemical Composition and Color Values Of Raw Materialssupporting
confidence: 93%
See 2 more Smart Citations
“…It is a traditional famous brand product in Hezhou, which is sold well in Guangxi and Guangdong with its "taste, quality and crispy" [3]. The main food of taro is corm, which contains rich starch, protein, dietary fiber, vitamins and minerals and so on [4]. In addition, it also contains active substances such as polysaccharides, phenol and flavonoids [5], which can benefit the stomach and broaden the intestine, defecate and detoxify, tonic the liver and kidney, prevent and cure diabetes, etc.…”
Section: Introductionmentioning
confidence: 99%